Noise pollution in the employees of the Adelca Acería factory in the city of Machachi - Aloag, Ecuador in the period 2022 - Zurita , Verónica; Bonilla , Dayana; Sifuentes , Jessy; Zambrano , Juliana (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
Introduction: Noise pollution in the ADELCA steel mill, located in the area of Alóag, Ecuador, was identified as a significant environmental and health problem. This phenomenon caused hearing problems in the employees and affected the inhabitants of the sector, in addition to generating a negative environmental impact due to the waste or slag produced by the steel. The World Health Organization (WHO) estimated that approximately 278 million people in the world suffer from hearing loss, 50% of which could be prevented through appropriate measures. This study focused on determining the levels of environmental noise to which ADELCA workers were exposed and describing the degree of annoyance perceived by them, thus assessing the impact of noise pollution in their work environment. Methods: A study was carried out in which digital surveys were applied to ADELCA employees to know their perception of noise and its relationship with noise pollution. These surveys were designed to identify the percentage of workers who considered noise as a significant polluting problem. In addition, environmental noise levels were measured at the plant and compared with the permissible limits established by the company’s regulations. Results: The results showed that a high percentage of the employees perceived noise as a major problem that affected both their well-being and their work performance. Also, the noise levels recorded exceeded the recommended values, which showed the need to implement corrective measures. Workers’ opinions reflected a consensus on the importance of mitigating noise to improve working conditions. Conclusions: The study concluded that noise pollution at ADELCA had a significant negative impact on employee health and the work environment. Based on the data collected, corrective measures were proposed that included reducing noise levels through technological and operational improvements. These actions achieved a positive impact by reducing noise levels to below permissible limits, thus improving the quality of life of workers and promoting a safer and more efficient work environment